Simulation Study on the Vibration Response of an EV Power Train Considering the Fluid-structure Coupling - Chen Shiyang; Yu Peng; Zhang Tong; Guo Rong (Jixie chuandong)
Taking a centralized drive electric vehicle power train as study object,considering the influence of coolant and lubricating oil,the fluid- structure model is established. The modal and vibration response of the model is researched. First,the fluid- structure model is proved to be correct by comparing its simulation result with the experimental result. Then,other two kinds of fluid- structure model,each one of which involved one kind of fluid,are established. The different influence degree of these two kinds of fluid on the model natural frequency is analyzed through modal simulation. At last,the power train vibration response under electromagnetic excitation is obtained by simulation,and it is compared with the result of the original model. The result indicates,that various dynamics phenomenon are showed by the model which considering the fluid- structure model with coolant,lubricating oil and mechanical components and the foundation for the subsequent optimization design is provided.